Numerical analysis of heat transfer and solid volume fraction profiles around a horizontal tube immersed in a supercritical water fluidized bed. (25th January 2016) - Lu, Youjun; Zhang, Tianning; Dong, Xubin
Highlights: Heat transfer in SCW and gas–solid fluidized bed with immersed tube was modeled. The comparison of heat transfer between two kinds of fluidized bed was conducted. The effects of inlet velocity on gas–solid and SCW fluidized bed were studied. High solid fraction will lead to low heat transfer coefficient in SCW fluidized bed. Abstract: In the present work, the heat transfer and solid volume fraction distribution characteristics in a supercritical water (SCW) fluidized bed with immersed tube are modeled with Two-Fluid model (TFM) incorporated with the Kinetic Theory of Granular Flow (KTGF). The Gidaspow drag model and Gunn heat transfer correlation are used to describe the interaction and heat transfer between different phases, respectively. A comparison between SCW and gas–solid fluidized bed was conducted. The results show that diameter and rising velocity of bubbles in the gas–solid fluidized bed are larger than that in the SCW fluidized bed when the corresponding fluidization numbers in both systems keep the same, and channeling is observed only in SCW fluidized bed. High particle concentration is always accompanied with high heat transfer coefficients around the tube in the gas–solid fluidized bed. In SCW fluidized bed, however, higher particle concentration will lead to lower heat transfer coefficients around the tube. Smaller fluctuations of solid volume fraction and heat transfer coefficients are also observed in the SCW fluidized bed than that in the gas–solid fluidized bed. In addition, the influence of fast fluid inlet velocity on solid volume fraction and heat transfer in SCW fluidized beds is considered.